The use of preexposure treatments for HIV prophylaxis - Majid A (Dove Medical Press, 2012)
Adrian Majid, Robert R Redfield, Bruce L GilliamInstitute of Human Virology, University of Maryland School of Medicine, Baltimore, MD, USAAbstract: Infection with human immunodeficiency virus remains a global concern with a significant number of incident infections still reported worldwide. The use of prophylaxis prior to exposure to the virus to prevent infection has been a growing area of recent research. Results in nonhuman primates and clinical trials in high-risk patient populations using preexposure prophylaxis have shown promising results in terms of efficacy and safety, especially relating to oral preexposure prophylaxis. The potential use of oral antiretroviral agents traditionally used for human immunodeficiency virus treatment as prophylaxis raises interesting considerations, such as the best agents available for such a role, long-term safety in healthy individuals, and the potential development of resistance to these agents should infection occur. From a public health perspective, the cost-effectiveness of implementing this preventive strategy has not been fully defined at this point in time.Keywords: preexposure prophylaxis, human immunodeficiency virus, tenofovir, maraviroc